Asas Oportunitas dalam Penegakan Hukum Pidana Korupsi: Studi Yuridis terhadap Kewenangan Jaksa - Muhammad Kurniawan Budi Wibowo; Zaenal Mustofa; Aris Sunindyo; Agus Marzuki; Aditya Fajri Kurnia Pradana (Faculty of Law, Universitas Pekalongan, 2025)
The principle of opportunity is a criminal law principle that gives prosecutors the authority not to continue prosecuting cases in the public interest. In Indonesia, although the legal system normatively adheres to the principle of legality, the practice of discretion by prosecutors in handling cases, including corruption, shows a tendency to apply the principle of opportunity which has not been strictly regulated. Corruption as an extraordinary crime demands strict, transparent and accountable law enforcement. However, the use of discretion by prosecutors in stopping corruption cases risks weakening public trust and opening up opportunities for abuse of authority. This research aims to juridically examine the position of the principle of opportunity in the Indonesian criminal law system and assess the prosecutor's authority in applying it in corruption cases. The research method used is normative juridical with statutory, conceptual, and comparative legal approaches. The results of the study show that there is a need for normative limits on the prosecutor's discretionary space, especially in corruption cases, as well as strengthening the external supervision mechanism. Comparative studies with countries such as the Netherlands and Japan show that the application of the principle of opportunity can be effective if supported by accountability and strict supervision. Therefore, legal policy reform in the form of codification of norms and transparency of law enforcement is an urgency in order to strengthen the integrity of the prosecutorial institution and the effectiveness of corruption eradication.